SISTEM INFORMASI PENERIMAAN BEA MASUK DI KPPBC NGURAH RAI - Banuaji, Armananda Didha; Firmansyah, Amrie (Politeknik Keuangan Negara STAN)
ABSTRACT This study aims to discuss the information system of import duty that focuses on the procedure of receipt of import duties, potential threats to each process and internal control that has been carried out. This study uses a case study at the Ngurah Rai Customs and Excise Supervision Office, whose main activity is providing services and supervision on the importation of goods. This research was conducted with descriptive qualitative methods carried out from April to July 2016. Import duty and tax cycle in the context of imports of imported goods that enter through cargo at the Ngurah Rai Customs and Excise Supervision Office start from the import notification of goods, payment and repayment of customs obligations to the general state cash account, the process of issuing goods, and reporting income. The Ngurah Rai Customs and Excise Supervision and Service Office, in general, has implemented an internal control system properly, but there are still some weaknesses from the implementation of internal controls at the Ngurah Rai Customs and Excise Service Office. This study suggests that the Directorate General of Customs and Excise need to develop alternative methods as an anticipatory step if there is interference with the Indonesia National Single Window. Also, the Ngurah Rai Customs and Excise Supervision Service Office needs to develop alternative methods as an anticipatory step if the Service User Portal and the Service Computer System experience interference. Keywords; import duty, state revenue information system, state revenue module ABSTRAK Penelitian ini bertujuan untuk membahas sistem informasi penerimaan bea masuk yang berfokus kepada prosedur penerimaan bea masuk, potensi ancaman pada setiap proses, dan pengendalian internal yang telah dilakukan. Penelitian ini menggunakan studi kasus di Kantor Pengawasan dan Pelayanan Bea dan Cukai Ngurah Rai yang kegiatan utamanya adalah memberikan pengawasan dan pelayanan importasi barang. Penelitian ini dilakukan dengan metode kualitatif deskriptif yang dilakukan selama periode April sampai dengan Juli 2016. Siklus pendapatan Bea Masuk dan Pajak Dalam Rangka Impor atas barang impor yang masuk melalui kargo pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Ngurah Rai dimulai dari pemberitahuan impor barang, pembayaran dan pelunasan kewajiban kepabeanan ke rekening kas umum negara, proses pengeluaran barang, serta pelaporan pendapatan. Kantor Pengawasan dan Pelayanan Bea dan Cukai Ngurah Rai secara umum telah melaksanakan sistem pengendalian internal dengan baik, namun masih terdapat beberapa kelemahan dari penerapan pengendalian internal di Kantor Pengawasan dan Pelayanan Bea dan Cukai Ngurah Rai. Penelitian ini menyarankan agar Direktorat Jenderal Bea Cukai perlu mengembangkan metode alternatif sebagai langkah antisipatif apabila Indonesia National Single Window dan Portal Pengguna Jasa maupun Sistem Komputer Pelayanan mengalami gangguan. . Kata Kunci; bea masuk, sistem informasi penerimaan negara, modul penerimaan negara